Influence of Smoking in the Clinical Outcomes of Distal Radius Fractures - Kaneko, Ayaka; Naito, Kiyohito; Obata, Hiroyuki; Nagura, Nana; Sugiyama, Yoichi; Goto, Kenji; Kawakita, So; Iwase, Yoshiyuki; Kaneko, Kazuo (Journal of Hand and Microsurgery, 2020)
Introduction There are various studies that reviewed the effect of cigarette smoking in fracture healing process. Nonunion, delayed union, and residual pain are the significant risk factors associated with smoking and fracture healing. Little has been known about the impact of smoking in distal radius fracture healing. We intend to explore in brief the effect of smoking in distal radius fracture healing and comparing it with nonsmokers having the same fracture fixation and analyze the outcomes with respect to fracture healing and return of function.Materials and Methods Of the total 186 patients, 92 were included in the study with (n = male: 31, female: 61) mean age of 60.2 years. They were divided into two groups: smoking (n = 43) and nonsmoking (n = 49). All had surgical fixation of the distal radius with volar locking plate and started on early mobilization. The range of motion of the wrist, grip, visual analog scale, quick disabilities of the arm and shoulder and hand score, Mayo wrist score, and bone healing period were noted between these two groups and compared with statistical analysis.Results The mean follow-up period was 8.7 months. There was a significant association of young age and male patients having distal radius fractures in the smoking group (p < 0.05). All fractures healed well in both groups without complications. There was no significant difference between these two groups in terms of range of motion, grasp, bone healing period, and functional outcomes.Conclusion Despite the well-known fact that, smoking has negative implications in the fracture healing process, we found group of patients (smoking and nonsmoking) with distal radius fractures treated by volar locking plates healed well with good radiological union and excellent functional outcome There is no significant influence of smoking in distal radius fracture fixation.
Keywords: smoking; distal radius fractures; nonunion; bone healing